La poétique du non-dit chez Jules Barbey d'Aurevilly - Wandzioch, Magdalena (Romanica Silesiana)
Magdalena Wandzioch investigates the poetics treating information as secret, revealing itself in the reader's pact, at the narration and character level, typical of Barbey d'Aurevilly. Keywords: Barbey d’Aurévilly; pact with the reader; narration; literary character; the poetics of concealing information <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />